(untitled) (Third Sector Social Economic Review, 2022)
Research on consumer behavior has moved to another dimension with the pandemic period. From this period, consumer behavior should be evaluated outside of traditional patterns. The science of consumer behavior researches the purchasing patterns of consumers in the markets and analyzes the factors affecting the purchasing behavior in question by evaluating the market conditions in which they are located. In a global sense, some economic crises, natural disasters or extraordinary situations such as pandemics cause differentiation in consumer needs and purchasing styles. All situations of extraordinary nature have a significant impact on consumer behavior. The main problem of our study is to reveal the relationships between consumer behavior and environmental conditions. Therefore, the aim of this study, what are the consumer purchasing changes that occur during epidemic periods, in which direction the changing behaviors of consumers during epidemic and disaster periods, and what developments or negativities the epidemic periods bring in the consumer market are examined. In the study, starting from the Covid-19 pandemic period, when the world was struggling and the first case was seen in Turkey in March 2020, consumer behaviors were examined in a periodic framework until today. The data were obtained by questionnaire and analyzed with SPSS. In the study, it was concluded that the shopping styles of consumers and the frequency of online shopping changed during the pandemic period.